Mode of death in heart failure: findings from the ATLAS trial. Issue 1 (1st January 2003) - Poole-Wilson, P A; Uretsky, B F; Thygesen, K; Cleland, J G F; Massie, B M; Rydén, L
Abstract : Objective: To investigate markers that predict modes of death in patients with chronic heart failure. Design: Randomised, double blind, three period, comparative, parallel group study (ATLAS, assessment of treatment with lisinopril and survival). Patients: 3164 patients with mild, moderate, or severe chronic heart failure (New York Heart Association functional class II–IV). Interventions: High dose (32.5 or 35 mg) or low dose (2.5 or 5 mg) lisinopril once daily for a median of 46 months. Main outcome measures: All cause mortality, cardiovascular mortality, sudden death, and chronic heart failure death related to prognostic factors using competing risks analysis. Mode of death was classified by trialists and by an independent end point committee. Results: Age, male sex, pre-existing ischaemic heart disease, increasing heart rate, creatinine concentration, and certain drugs taken at randomisation were markers of increased risk of all cause mortality and cardiovascular death. There were risk markers for sudden death that were different from the risk markers for death from chronic heart failure. Low systolic blood pressure at baseline, raised creatinine, reduced serum sodium or haemoglobin, and increased heart rate were associated with chronic heart failure death. Use of β blockers or antiarrhythmic agents (mainly amiodarone) was associated with a reduced risk of sudden death, whereas long acting nitrates and previous use of angiotensin converting enzyme inhibitors were markers for increased risk. Conclusions: The use of competing risks analysis on the data from the ATLAS study has identified variables associated with certain modes of death in heart failure patients. This approach to analysing outcomes may make it possible to predict which patients might benefit most from particular therapeutic interventions.